Improvement of Murrah Buffalo Milk Production Fed Palm Oil Solid Waste Containing Ration - P Mahyuddin (Media Peternakan, 2010)
A field trial was conducted to study the effect of dietary inclusion of palm oil solid waste on milk production of murrah buffalo raised under palm oil plantation. Two farms from different districts were involved in this study.  Forty cows with 7-9 month pregnancy were selected from each farm and they were divided into control and treatment groups.  Cows in control group were offered a mixed supplement of 1 kg copra meal + 2 kg fresh grated cassava root + mineral mix  and treatments group were offered the control diet + 1 kg palm oil solid waste. The dietary supplement was offered to the cows for 2 months before and 2 months period after calving. The cows were grazed under palm oil plantation. The addition of palm oil solid waste in the diet improved (P < 0.05) milk yield (8.5 l/d vs 10.5 l /d), calves weight at birth (19.6 kg vs 22.1 kg) and live weight gain of the calves (0.66 kg/d vs 0.99 kg/d). Additional dietary inclusion of palm oil solid waste improved milk yield of murrah buffalo, and further improvement of milk yield was expected to achieve by higher inclusion of palm oil solid waste in the diet.